Women Academic Leadership in Islamic Higher Education: Embracing the Society 5.0 Era - Hadiati, Eti; Dwiyanto, Agus; Setianingrum, Diah Ayu; Jatmiko, Agus; Iqbal, Iqbal (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2025)
This study explores the transformational leadership experiences of women academic leaders in Islamic higher education institutions in Bandar Lampung, Indonesia, within the context of Society 5.0. Employing a phenomenological qualitative method, the study conducted in-depth interviews with five leaders and an Information Technology expert. Primary data were collected through in-depth interviews with five women academic leaders serving as Vice Rector, Dean, Head of Study Program, and Secretary of Study Program. An additional interview was conducted with the Information Technology expert as part of expert triangulation, enriching the study’s perspective on the implications of technological integration in academic leadership. The results indicate a consistent tendency towards transformational leadership, which is considered the most adaptive and sustainable model for addressing rapid social and digital changes. Participants emphasized the importance of emotional connection, ethical foundations, and collaborative innovation as key components of effective leadership in the Society 5.0 era. Furthermore, this study shows that transformational leadership enables institutions not only to adapt to technological advancements but also to maintain a humanistic and inclusive academic culture. These findings have significant implications for leadership development in Islamic higher education, underscoring the importance of vision, moral integrity, and empathy in navigating future complexities.